Pengukuran Overall Equipment Effectiveness dan Model Optimasi untuk Meminimalkan Production Losses - Ginantaka, Aditia; Lesmana, Tubagus Teja (JURNAL AGROINDUSTRI HALAL, 2024)
The overall equipment effectiveness assessment (OEE) result on the rollwrap machine at Sugar Candy Co.Ltd reached 69.1%. This OEE result needs to meet the requirement of companies that apply OEE values above 72.5%. The Purpose of this research is to analyze the effectiveness of the roll wrap machine and identify the cause of its ineffectiveness of the machine. Besides, this study also uses a fuzzy inference system to classify the variables of downtime losses, frequency of speed losses, and OEE into linguistic variables to make it easier for operators to identify machine status. Improvement plan with a proposed quantitative approach using goal programming by minimizing deviational variables at low, medium, and high OEE status frequencies. The research results show that unscheduled machine maintenance reduces machine performance and is the main factor causing low machine availability. There were nine fuzzy rules for the machine OEE status inference process at high, medium, to low-status levels. Based on the calculation of goal programming, to achieve the OEE target above 80% within 30 working days, The OEE status must achieve the high level at least 20 times. The machine can achieve OEE with a moderate level eight times, and a low level occurs a maximum of two times.